1998
DOI: 10.1046/j.1365-2141.1998.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Should a platelet limit of 600 × 109/l be used as a diagnostic criterion in essential thrombocythaemia? An analysis of the natural course including early stages

Abstract: Summary. In order to evaluate the natural history of essential thrombocythaemia (ET), clinical data and prognostic factors of 143 patients with ET were retrospectively analysed (mean observation time 6·1 Ϯ 4·6 years). In 42 patients the early phase of the disease with initial platelet counts between 250 and 600 × 10 9 /l was assessed. In most early cases, ET was suggested by clinical symptoms (79%) and increased megakaryopoiesis (95%) with abnormal megakaryocytes in bone marrow histology (n ¼ 34) and cytology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 25 publications
(24 reference statements)
5
94
0
2
Order By: Relevance
“…Actually, only one patient in the latter subgroup of 36 patients had a MVC during the follow-up period. These results are in accordance with those previously reported by others investigators, 5,9,10 and reinforce the appropriateness of a wait-and-see approach for young ET patients, as previously recommended. 21 In our series, a history of previous vascular complications or the presence of major ischemic events at the time of ET diagnosis were also strongly linked to the risk of subsequent vascular complications, as also pointed out by others.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Actually, only one patient in the latter subgroup of 36 patients had a MVC during the follow-up period. These results are in accordance with those previously reported by others investigators, 5,9,10 and reinforce the appropriateness of a wait-and-see approach for young ET patients, as previously recommended. 21 In our series, a history of previous vascular complications or the presence of major ischemic events at the time of ET diagnosis were also strongly linked to the risk of subsequent vascular complications, as also pointed out by others.…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, cigarette smoking has been related to a greater incidence of arterial ischemic complications in ET patients in some, 7 but not all studies, 5,10 whereas such an association has not been observed for diabetes and hypertension. 5,10 On the other hand, the lack of predictive value of platelet counts, in agreement with the results obtained in most Actuarial probability of appearance of major vascular complications (MVC) in 148 ET patients (a), and according to age group (b), the history or not of previous vascular complications at time of ET diagnosis (c), and the presence or absence of hypercholesterolemia (d). The dotted lines in each figure indicate the adjusted probability of developing MVC when the other significant covariates remain unchanged.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations